EXAMINING THE ROLE OF COMPUTERS IN THE TEACHING AND LEARNING OF GEOGRAPHY AT ADVANCED LEVEL: A FOCUS ON SIX HIGH SCHOOLS IN WARREN PARK/ MABELREIGN DISTRICT, ZIMBABWE - SAMKANGE, Dr. Wellington (IJRDO- Journal of Educational Research, 2016)
The advent of modern technology has been a welcome development in education. It is adevelopment that was envisaged to make teaching and learning easier, enjoyable andaccessible to all who require it. E-learning has now been used to support the traditionalmethods of teaching and learning. The introduction of computers in education has witnesseda change from the traditional approaches to teaching to the use of computer assistedinstruction (CAI). To support the use of modern technology, the Zimbabwean governmenthas distributed computers to both primary and secondary schools. To complementgovernment effort, parents and other stakeholders through School Development Committees,School Development Associations and Old Students Associations have contributed to theacquisition of educational resources that include computers. All these efforts were meant tofacilitate teaching and learning in schools. Despite these efforts the performance inGeography at Advanced level has remained low compared to other subjects. The purpose ofthe study was to examine the extent to which computer assisted instruction (CAI) has beenutilised in the teaching of Geography at Advanced level. The study also made an analysis ofother approaches used in the teaching and learning of Geography. The study used the mixedmethodology and the descriptive survey design. Data was collected using structuredquestionnaires, open-ended questionnaires, and face-to-face interviews. The six schools wereconveniently sampled and the respondents were randomly selected. The study concluded thatthere are many factors that have contributed to poor performance in Geography at A level.Some of the factors that emerged were lack computer skills for both teachers and pupils.There was limited use of computers in map work. Other areas that did not receive seriousconsideration in the teaching and learning of Geography were field work and hands- onapproach to teaching and learning Geography as a subject. The study recommends that therebe a paradigm shift in terms of the methods used in the teaching and learning of Geography atAdvanced level.